Production of IL-35 by Bregs is mediated through binding of BATF-IRF-4-IRF-8 complex to il12a and ebi3 promoter elements. Issue 6 (17th August 2018) - Yu, Cheng-Rong; Choi, Jin Kyeong; Uche, Anita N; Egwuagu, Charles E
Abstract: IL-10 and IL-35 suppress excessive immune responses and therapeutic strategies are being developed to increase their levels in autoimmune diseases. In this study, we sought to identify major cell types that produce both cytokines in-vivo and to characterize mechanisms that regulate their production. Experimental autoimmune uveitis (EAU) is a CNS autoimmune disease that serves as model of human uveitis. We induced EAU in C57BL/6J mice and investigated whether T cells, B lymphocytes, or myeloid cells are the major producers of IL-10 or IL-35 in blood, lymph nodes (LNs), spleen, and at the site of ocular inflammation, the neuroretina. Analysis of these tissues identified B cells as the major producers of IL-10 and IL-35 in-vivo. Compared to regulatory T cells (Tregs), IL-10- or IL-35-producing regulatory B cells (Bregs) are substantially expanded in blood, LNs, spleen, and retina of mice with EAU. We performed EMSA and chromatin immunoprecipitation (ChIP) assays on activated B cells stimulated with IL-35 or TLR agonists. We found that BATF, IFN regulatory factor (IRF)-4, and IRF-8 transcription factors were recruited and bound to AP1-IRF-composite elements (AICEs) of il12a, ebi3, and/or il10 loci, suggesting their involvement in regulating IL-10 and IL-35 transcriptional programs of B cells. Showing that B cells are major source of IL-10 and IL-35 in-vivo and identifying transcription factors that contribute to IL-10 and IL-35 expression in the activated B-cell, suggest that the BATF/IRF-4/IRF-8 axis can be exploited therapeutically to regulate physiological levels of IL-10/IL-35-Bregs and that adoptive transfer of autologous Bregs might be an effective therapy for autoimmune and neurodegenerative diseases. Regulatory B cells are major producers of IL-35 during experimental autoimmune uveitis and BATF-IRF-4-IRF-8 transcription factor complex regulates IL-35 transcriptional program in B cells.